CFD simulation and experimental analysis of flow dynamics and grinding performance of opposed fluidized bed air jet mill - Munusamy, Sri Raj Rajeswari (2011)
This paper presents a three dimensional Computational Fluid Dynamics (CFD) model to investigate the flow dynamics of solid–gas phases during fine grinding in an air jet mill. Alpine 100AFG fluidized bed air jet mill is considered for the study and the jet milling model is simulated using FLUENT 6.3.2 using a standard k-ε model. The model is developed in GAMBIT 2.3.16 and meshed by tet/hybrid (T-Grid) and Triangular (Pave) meshes. The effects of operating parameters such as solid feed rate, grinding air pressure and internal classifier speed on the performance of the jet mill are analyzed. The CFD simulation results are presented in the forms of dual phase vector plot, volume fraction of phases and particle trajectories during fine grinding process. Themass of ground feed entering and leaving the cyclone (underflow) is also computed by simulation. The proposed model gives realistic predictions of the flow dynamics within the jet mill. Experiments are conducted on the Alpine 100AFG jet mill to study the particle size, morphology and mass of the ground product. The numerical results are found in good agreement with the experimental results.